KERJASAMA LEMBAGA PEMBERDAYAAN MASYARAKAT (LPM) KUTA DENGAN KEPOLISIAN DALAM MENANGGULANGI TINDAK PIDANA PENCURIAN - Kumala Dewi, Ni Komang Ratih (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
The rampant of crime of theft by pickpocket mode in the Kuta area has given a negative impact on tourism. In Kuta area, there are an institution is engaged in community empowerment which is called Lembaga Pemberdayaan Masyarakat (LPM). LPM has a mission which is participate to increase law awareness and encourage law enforcement, through this mission was related a cooperation from police Department and LPM. Therefore, it is important that is studied in depth about the cooperation of LPM and Police Department in mitigating the crime of theft by pickpocket mode in Kuta area and also its constraints and prevention effort. The method of research which used is the empirical law research by the qualitative descriptive method. The data consists of primary data and secondary data. The technique of collecting data which is used the document study and interview technique. The technique of determine the sample used non probably sampling. The result found that the LPM role is to assist the police officer if it found a crime in area when the jagabaya and hansip (security officer) do their job. Related to the constraints which is faced by LPM and police officer that LPM does not has infrastructure, technical, and administrative. It is also does not has a legal protection to do investigation. Those constraints is tried to fulfill by the police officer and LPM however the legal protection of LPM is still does not found a solution. The role of LPM is still assist to catch and prosecute the executants in a while.
Keywords: cooperation; police department; LPM; crime of theft; mitigating effort